Merger Strategy of Regional Development Bank Sharia Business Units (UUS BPD) to Enhance the Market Share of Islamic Banking in Indonesia - Rohandi, Dadang (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2026)
Indonesia's Islamic banking sector continues to face challenges in expanding its market share relative to conventional banking. As of 2023, the market share of Islamic banking assets remains below 11%, a figure far below the global Islamic financial market leader, Malaysia, at 31%. One critical structural bottleneck is the inadequate capitalization and fragmented operations of Sharia Business Units (UUS) belonging to Regional Development Banks (BPD). This article evaluates the strategic viability of consolidating all UUS BPD through a merger scheme as a means of accelerating the spin-off mandate under Law No. 21 of 2008 and POJK No. 12/POJK.03/2020. Using a quantitative approach with time-series analysis and the least squares method, this study projects the post-merger market share trajectory of Indonesian Islamic banking through 2023. Simulation results indicate that a merger of UUS BPD, with Bank BJB Syariah as the surviving bank, would increase the aggregate Islamic banking market share from 6.92% to approximately 9.33%, and the least squares projection suggests that with sustained growth, the 10.67% threshold is attainable by 2023. The merger model is further evaluated through the lens of Maqashid al-Shariah, demonstrating alignment with the five universal objectives of Islamic law. This study contributes to the scarce literature on BPD-specific Islamic banking consolidation strategy in Indonesia and provides actionable policy recommendations for regulators and stakeholders.